The Effectiveness of The Use of Whiteboard Animation Media to Improve The Ability to Design Classroom Action Research - Aini Indriasih (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
Complaints about the lack of Open University tutors using learning media in tutorials impact the low quality of the final results of the Class Action Research course. This research aims to improve the ability of students to design classroom action research. Data was collected through a questionnaire given to Elementary School Teacher Education Students in Pati Districts. Qualitative data analysis is processed descriptively to determine the validity of media material whiteboard animation and its usefulness. The results showed that Whiteboard Animation media as a tutorial media for Class Action Research courses was able to increase motivation and help in learning. Whiteboard animation media positively influences students' ability to design classroom action research. This positive influence is shown through the rerata value achieved by the class utilizing Whiteboard Animation of 88.52 compared to the average value of 72.63 in the class without using media whiteboard animation.